Analisis Distribusi Frekuensi dan Uji Chi-Square pada Laju Pertumbuhan Penduduk dan Kepadatan Penduduk di Provinsi Kalimantan Tengah, 2023 - Gedeon Gedeon; Yudha Rinsaghi; Tantri Tantri; Jadiaman Parhusip (Asosiasi Profesi Telekomunikasi dan Informatika Indonesia, 2024)
This study analyzes demographic data from regencies/cities in Central Kalimantan Province, including population, population growth rate, population percentage, population density per km², and sex ratio. The results of the analysis show significant differences between regencies/cities, with population growth rates ranging from 0.98% to 1.97% per year. The highest population density was recorded in East Barito, while Lamandau had the lowest density. The sex ratio tends to show a male dominance, with Lamandau having the highest ratio. These findings provide an overview of the challenges and opportunities in development planning, as well as the need to design policies that are in accordance with the demographic characteristics of each region. A deeper understanding of this data is expected to support more effective policies in population management and development in Central Kalimantan.